THE ROLE OF MASS MEDIA IN ERADICATING CORRUPTION - YOHANES BERCHEMANS EBANG (Asia Pacific Fraud Journal, 2016)
So far, Indonesia has never been able to escape from the entanglement of corruption. This fact requires all elements of the nation to participate actively in combating this social scourge. Given that Indonesia is a democratic state, where the people are the holder of supreme power, the people have an important role in uncovering and combating the problem of corruption. One of the role and participation of the public is through the media. The reason is because the mass media can reach all levels of society. The mass media is a strategic tool that is able to sniff out and dismantle the rotten practices that start emerging or still veiled. The fact proves that in various places in Indonesia and abroad, corruption is always associated with the mass media.